Nucleolin Rescues TDP-43 Toxicity in Yeast and Human Cell Models - Peggion, Caterina; Massimino, Maria Lina; Stella, Roberto; Bortolotto, Raissa; Agostini, Jessica; Maldi, Arianna; Sartori, Geppo; Tonello, Fiorella; Bertoli, Alessandro; Lopreiato, Raffaele (Frontiers in Cellular Neuroscience, 2021)
TDP-43 is a nuclear protein involved in pivotal processes, extensively studied for its implication in neurodegenerative disorders. TDP-43 cytosolic inclusions are a common neuropathologic hallmark in amyotrophic lateral sclerosis (ALS) and related diseases, and it is now established that TDP-43 misfolding and aggregation play a key role in their etiopathology. TDP-43 neurotoxic mechanisms are not yet clariﬁed, but the identification of proteins able to modulate TDP-43-mediated damage may be promising therapeutic targets for TDP-43 proteinopathies. Here we show by the use of refined yeast models that the nucleolar protein nucleolin (NCL) acts as a potent suppressor of TDP-43 toxicity, restoring cell viability. We provide evidence that NCL co-expression is able to alleviate TDP-43-induced damage also in human cells, further supporting its beneficial effects in a more consistent pathophysiological context. Presented data suggest that NCL could promote TDP-43 nuclear retention, reducing the formation of toxic cytosolic TDP-43 inclusions.